Psychological influences and implications for household disaster preparedness: a systematic review - Ni, Minrui; Xia, Liang; Wang, Xinru; Wei, Yixuan; Han, Xiaofei; Liu, Yiqiao; Pan, Song (Frontiers in Public Health, 2025)
IntroductionHousehold disaster preparedness remains critical yet underachieved, despite substantial investments in mitigation infrastructure. Understanding psychological drivers affecting the implementation of household preparedness measures helps distinguish families fully prepared for disasters from those not, thereby improving disaster education. Psychological drivers may promote, hinder, or have no impact on household preparedness. This review fills a significant gap by systematically categorizing psychological factors influencing household disaster preparedness, an area that remains underexplored in previous literature, aiming to provide recommendations for developing more effective psychological interventions and coping mechanisms.MethodsA systematic literature search was conducted using PRISMA guidelines, analyzing published studies (2017-2024) from Web of Science, Google Scholar, and ScienceDirect. Two authors determined the eligibility of studies based on the inclusion and exclusion criteria.ResultsA total of 35 studies were included in this review. Regarding cognitive appraisal, risk perception generally promotes household preparedness. Hazard intrusiveness, perceived efficacy, and perceived response efficacy encourage preparedness. Regarding motivation and intention, self-efficacy and perceived benefits boost preparedness, and the transfer of responsibility regulates the influence of trust on household preparedness. Regarding social interaction, formal support, and community resilience promotes preparedness, whereas informal support and social norms may impede it. Regarding bonds with the living environment, place attachment promotes housing protection but hinders relocation. Sense of place hinders permanent evacuation or relocation.DiscussionDisaster prevention and management should emphasize the responsibility of individuals and families in reducing disaster risks, clarify the consequences and probabilities of disasters, refine social norm indicators, and develop a resettlement planning incorporating place identity cultivation to improve effective household preparedness.